Implications of industry 5.0 on environmental sustainability - Sajid, Muhammad Jawad 1989-; Khan, Syed Abdul Rehman 1987-; Yu, Zhang 1990- (Practice, progress, and proficiency in sustainability (PPPS) book series, 2023)
On the tenth anniversary of Industry 4.0, the European Commission (EU) launched Industry 5.0. Industry 4.0 is thought to be driven by technology, whereas Industry 5.0 is driven by value. Most businesses are still grappling with the definition and implementation of Industry 4.0, but there is already discussion of the next industrial revolution: Industry 5.0. Industry 4.0, with the emergence of automation technologies, the Internet of Things (IoT), and the smart factory, developed the preceding layer. Industry 5.0 advances by harnessing the combination of more powerful and precise machines and the unique creative potential of human beings. The next wave of the industrial revolution must define how we collaborate and set the principles of human-machine interaction. The coexistence of two industrial revolutions raises problems, necessitating debate and clarification. In particular, the implications of industry 5.0 on environmental sustainability can help with the environmentally sustainable adoption of the 5th industrial revolution.